PENGARUH KOMPENSASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU PADA SMK 2 SWASTA PERKUMPULAN AMAL BAKTI SUMATERA UTARA - Ibnu Hajar Nasution; Hasrudy Tanjung; Bahril Datuk (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
The purpose of this study, among others, is to determine and analyze the effect of compensation, job satisfaction and organizational commitment on teacher performance at private vocational high school 2, North Sumatran Charity Association. This research is included in quantitative research because the approach used for research proposals, processes, hypotheses, going to the field, data analysis, data conclusions to writing uses aspects of measurement, calculation, formula and certainty of numerical data. The subject of the study was a private high school teacher 2, North Sumatran Charity Association. The data were analyzed using multiple linear regression formulas and hypothesis testing. The results showed that simultaneously the Fcount value of 11.009 was greater than the Ftable value of 2.807 and the significance value of 0.000 was less than 0.05. This indicates that the results of the study reject H0. Thus, simultaneously Compensation (X1), Job Satisfaction (X2), and Organizational Commitment (X3) have a positive and significant effect on Teacher Performance.